PENGAJIAN TASAWUF K.H. MUHAMMAD RIDWAN BASERI DI MAJELIS TAKLIM AL-HIDAYAH HULU SUNGAI SELATAN (TELAAH KARISMA DAN TASAWUF MODERN) - Zulkifli, Zulkifli (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
This study focused on the figure of KH Muhammad Ridwan Baseri who is popularly known as Guru Ridwan Kapuh. This figure is a charismatic ulama in Hulu Sungai Selatan regency, South Kalimantan, in the study of Sufism. This research is a field research using descriptive analysis and sociological approach which refers tobehavioral aspects implemented in Al-Hidayah located in Kapuh Simpur, Hulu Sungai Selatan. This studyexplained thatGuru Ridwan Kapuh is the descendantof Datu Kalampayan, and the student of Guru Sekumpul Martapura. Sufism gives a strong color to Guru Ridwans life. He teaches the book of tasawuf in accordance with the present context, for example mahabbah, trust, ascetic/zuhud in the present context.